Truncal pulsion in acute ischemic stroke – Clinico-anatomical correlation - S, Sheetal; Sasidharan, Aswathy; Thomas, Reji (Nepal Journal of Neuroscience, 2021)
Context: Truncal pulsion is a compelling sensation of being pulled to one side, in the context of normal motor and sensory functions and normal co-ordination. It is seen in a variety of ischemic strokes. Aims: This article aims at identifying ischemic stroke syndromes associated with truncal pulsion, with review of the neural substrate responsible, to help in recognition and reporting. Settings and Design: This was a prospective study conducted at Department of Neurology, at Pushpagiri institute of medical sciences and research centre, Thiruvalla, Kerala, India, over a period of 5 years, among patients with acute ischemic stroke. Methods and Material: We studied all patients with acute ischemic stroke, who were admitted to our department, over a five-year period. Patients presenting with truncal pulsion were shortlisted and were assessed by investigators independently. All patients underwent MRI brain, which was assessed by investigators 1 and 2, independently. The demographic profile, risk factors, clinical features, neuroimaging findings and outcomes were analysed using SPSSv21. Results: A total of 1456 patients with acute ischemic strokes were identified, of which 27 with truncal pulsion were included in the study. The common sites of infarction resulting in truncal pulsion were lateral medulla, cerebellum, thalamus, pons and midbrain. One patient had infarct involving anterior cingulate. Truncal pulsion was ipsilateral in infarcts involving medulla and cerebellum and contralateral in infarcts involving the pons, midbrain, mesencephalo-diencephalic junction, thalamus and cingulate. Conclusions: Truncal pulsion, a compelling sensation of falling, is a disabling symptom occurring in a variety of strokes and it poses significant challenge in neuro-rehabilitation.